Technical efficiency analyses in hospitals of Tabriz University of Medical Sciences - Feizollah Akbari; Mohammad Arab; Khosro Keshavarz; Alireza Dadashi (Tehran University of Medical Sciences, 2012)
Background: The hospital is one of the main organizations which offering health care and medical services in a high level allocated sources in the health sectors. Therefore, considering to efficiency costs is great importance. This study aims in considering the efficiency of the hospitals of Medical University in Tabriz, Iran, by using Data Exhaustive Analysis Method.Materials & Methods: The study inspected and analyzed the technical efficiency and also effective factors on it in selected hospitals by using Data Exhaustive Analysis Method during the 3 period years (1384-1387). In order to conduct this study, the comprehensive Input-oriented Form of Data Exhaustive Analysis Method assuming in the variable return compared with the scale. The variables of the inputs in this study included number of physicians, non-physician staff, and active bed and annual costs of the hospital. The variables of the outputs included the coefficient of the occupied beds, number of admitted patients, and surgeries. To data analyzing, SPSS and data envelopment analysis software were used. It is worth mention that the data in this study were accumulated by using the forms devised by the authors and standardized questionnaire via referring and going to the hospitals.Results: The findings of data exhaustive analysis method showed that there was %5(TE=0/953) possible capacity augment in the technical efficiency. The findings also suggest that there is a potential frugality in consuming the inputs in order to produce a constant amount of the output. Meanwhile, there is a potential augment of the output by using a constant amount of the input, as well. The findings also represent the effect of the demographic factors and functional factors on the efficiency of the hospitals.Conclusion: It is suggested that to leave out the surplus staff, decrease the surplus costs of the hospital through replacing the energy consumption and a proper management of energy and other surplus inputs, hire sophisticated managers and applying the graduated field of management in health care and medical services and also hire the managers with high quality degrees, create the data envelopment analysis of enhancing efficiency should be one of the useful way to provide qualified medical services in our society as a comprehensive programming. Based on the findings of the data Exhaustive analysis method, improving the efficiency of the hospitals, health care system and medical section are essential as well.